Associations of MDM2 rs2279744 and TP53 rs1042522 polymorphisms with cervical cancer risk: A meta-analysis and systematic review - Yu, Meijia; Zhang, Qin; Zhao, Xia (Frontiers in Oncology, 2022)
ABSTRACT Background: Although the association between MDM2 rs2279744 and TP53 rs1042522 polymorphisms and cervical cancer has been reported, the results of its correlation were contradictory. Thus, we conducted a meta-analysis to precisely verify the relationships between MDM2 rs2279744 and TP53 rs1042522 polymorphisms and cervical cancer. Methods: We thoroughly searched the PubMed, Web of Science, Embase, and Scopus databases for all potential articles from inception to June 2022 and used R Version 4.1.2 and STATA software 12.0 for the meta-analysis. The odds ratios (ORs), 95% confidence intervals (CIs) and 95% prediction intervals (PIs) were calculated to evaluate the associations. Subgroup analyses stratified by ethnicity, source of control, quality score and adjustment were further conducted to assess the relationship between MDM2 rs2279744 and TP53 rs1042522 polymorphisms and cervical cancer. Results: A total of 30 case-control studies involving 5025 cases and 6680 controls were included. All the included studies were population-based or hospital-based studies. The overall analysis showed that MDM2 rs2279744 polymorphism was closely related to an increased risk of cervical cancer in the recessive model (GG vs GT + TT: OR = 1.602, 95% CI: 1.077-2.383, P = 0.020) and homozygote model (GG vs TT: OR = 1.469, 95% CI: 1.031-2.095, P = 0.033, 95% PI: 0.516-4.184). A significant correlation between TP53 rs1042522 polymorphism and cervical cancer was observed in two models (CC + CG vs GG: OR = 1.759, 95% CI: 1.192-2.596, P = 0.004, 95% PI: 0.474-6.533; GG vs CC: OR = 2.442, 95% CI: 1.433-4.162, P = 0.001, 95% PI: 0.456-13.071). Conclusions: This meta-analysis revealed that MDM2 SNP309T>G and TP53 rs1042522 C>G polymorphisms were associated with the increased risk of cervical cancer.